Effect of Supplementation of Area Specific Mineral Mixture on Performance of Crossbred Cows with Reproductive Disorders in Kakatpur Block - Satapathy, Debasish; Mishra, S.K.; Swain, R.K.; Sethy, Kamdev; Sahoo, Gyana Ranjan (Indian Journal of Animal Nutrition, 2018)
The experiment was conducted to evaluate the effect of area specific mineral mixture on growth performance, blood parameters and reproductive efficiency in crossbred cows in Kakatpur block of Odisha. Forty crossbred animals were selected for the experiment and divided in to two equal groups. Among them number of anestrus animals and repeat breeder animals were 14 and 26, respectively. Therefore, each group had 7 anestrus and 13 repeat breeder animals. The animals in control group (T1) were fed as per farmers’ practice while in groupT2, the animals were supplemented with area specific mineral mixture @ 50 g/d/animal for a period of 60 days. After the experiment, higher (P<0.05) ADG and BCS were observed in group T2 (199.51±8.62 g/d and 3.93±0.02) as compared to group T1 (143.66±8.50 g/d and 3.02±0.03). Blood glucose and Hb levels were higher (P<0.05) in group T2 after the treatment. The serum mineral concentration increased (P<0.05) in group T2. Percentage of animals having nonfunctional and sub-active ovaries was reduced leading to higher level of functional ovaries in group T2. A higher percentage (55%) of animals in group T2 conceived as compared to that of 15% in group T1 at the end of the experiment. So, supplementation of area specific mineral mixture @ 50 g/d/ animal resulted in higher ADG, BCS, blood glucose, Hb and also better reproductive health of the animals.